Conducting school-based research during Covid: evaluating the Silver Stories programme. Issue 3 (4th May 2023) - Koutsouris, George; Nash, Tricia; Norwich, Brahm
ABSTRACT: This paper presents findings from a small-scale pilot evaluation of the Silver Stories programme. Silver Stories involves school-age children reading to older people in the community and is a way of addressing literacy and emotional difficulties, as well as enhancing wellbeing. The authors collected and analysed questionnaire and interview data after a school term of programme implementation, across five schools in England and Wales, during the period of the third lockdown. The main finding was that participants experienced the programme as an opportunity for relationship-building between generations, highlighting the relational nature of reading as a 'literacy event' and wellbeing as a product of social interaction rather than an individual attribute. The pilot also indicated that school priorities might have shifted due to COVID-19 from academic attainment to a focus on social and emotional support. Although this was likely a temporary phase, it is also an opportunity to build back better.